Globalizing Small Businesses: Harnessing Human Capital for Digital Marketing Success - Choirul Anam; Iva Khoiril Mala; Imam Mukhlis; F. Danardana Murwani (Jurnal Manajemen Kreatif dan Inovasi, 2024)
In the contemporary landscape of globalization, small and medium-sized enterprises (SMEs) face escalating challenges in navigating international markets. This research purpose to explore the pivotal role of human capital in propelling the internationalization of SMEs, particularly through the lens of digital marketing. The research methodology involved document analysis to understand global market dynamics and the key role of human capital in optimising digital marketing for international expansion. The main results show that investment in human capital development and digital capability enhancement are key factors in the successful internationalisation of SMEs. The findings provide an in-depth understanding of how SMEs can effectively utilise their human capital in the face of increasingly complex global market challenges. Overall, this article concludes that the integration of strong human capital with digital marketing strategies can contribute significantly to the successful internationalisation of SMEs and has important implications for the future development of SMEs in an era of globalization.